Pengembangan Modul Fisika Berbasis Saintifik Berbantuan QR Code Pada Materi Termodinamika Kelas XI - Nuku Hiva Hariyanto; Dasmo Dasmo; Asep Setiadi (Schrodinger Jurnal Ilmiah Mahasiswa Pendidikan Fisika, 2022)
This study aims to determine the module development process, the feasibility of the module and the response of students to the development of scientific-based thermodynamics learning modules with the help of a qr code. In this case, the qr code serves as a link to access various learning videos, as well as questions in the learning module. The method used in this research is research and development. The model used is a 4-D model. The development of the 4-D model consists of 4 stages, namely Define, Design, Development, and Disseminate. The scientific-based thermodynamics learning module assisted by qr code was declared feasible to use with validation from material experts 90.97% with very reasonable interpretation, media experts 77.50% proper interpretation and linguistic experts 92.50% very proper interpretation. And the response test was 30 students with a score of 87.20% in the very good category.